Checklist of marine algal floras from Paramushir and Shumshu (Northern Kuril Islands) - Nina G. Klochkova; Tatyana A. Klochkova (Acta Biologica Sibirica, 2025)
This study provides the most comprehensive checklist of marine macroalgae to date for Paramushir and Shumshu Islands (Northern Kuril Islands), based on recent field collections and a critical review of historical records. The resulting flora comprises 192 species (33 Chlorophyta, 115 Rhodophyta, 44 Phaeophyceae), extending the known flora of Paramushir by 17 species and that of Shumshu by 37 species. A standout finding is the discovery of Alaria marginata, which represents a first record for the entire Russian Far Eastern seas. Furthermore, we report a dense population of Feditia simuschirensis near Paramushir, indicating this kelp is not endemic to Simushir Island and necessitating a revision of its biogeographic status. In total, 17 species are newly reported for the Northern Kuril Islands, significantly enhancing the understanding of North Pacific phytogeography.